An improvised Van-De-Graaf generator - Topacio, Antoinetta Balingit 1952- (1977)
The purpose of the study was to conduct a feasibility study on improvising a Van-de-Graaf Generator, and to develop the improvised apparatus with high school students by doing some activities on the concept of the nature, transfer and effects of charges. Through experimentation, the study showed that locally available materials as substitute for aluminum dome, rubber belt electron conveyor, and metal rollers, that was made into an improvised apparatus could be used in activities and experiments in the study of charges and static electricity.